Meningitis [ cellular and molecular basis - Christodoulides, Myron (Advances in Molecular and Cellular Microbiology, 2013)
Examining meningitis mainly from a bacterial perspective, but also including an overview of viral, fungal and chronic meningitis, this book describes the anatomy of the meninges and clinical signs and symptoms of meningitis. Individual organisms that case meningitis worldwide are dealt with in specific chapters, describing in detail how these pathogens interact with the human host at both a molecular and cellular level, providing a thorough understanding of bacterial virulence factors and host cell response.